PENERAPAN E- GOVERNMENT DALAM PELAYANAN PUBLIK DI KELURAHAN TONDO KOTA PALU - Gatot Susanto; Syahruddin Hattab; Suasa Suasa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the extent to which the application of E-Government is implemented in public services at the Tondo Village Office, Mantikulore District, Palu City, which is studied based on the theory of Application of E-Government or Electronic Service Systems by Richardus Eko Indrajit (2004) with three aspects / elements namely Support, Capacity, Value and this research uses a qualitative descriptive approach method. Based on the results of this research, the researcher concluded that the Implementation of E-Government in Public Services at the Tondo Subdistrict Office from several aspects/elements which are used as references in this research are as follows: Support, support from policy stakeholders in the form of Regulations, Implementation of E-Government. -Government in Tondo Village is regulated by Palu City Regional Regulation Number 10 of 2015 concerning the Implementation of One-Stop Integrated Services Article 1 which supports the implementation of E-Government within the Palu City Government. Capacity (Capabilities/Resources), Availability of financial resources originating from APBD funds and the availability of sufficient supporting facilities to support the implementation of E-Government at the Tondo Village Office. Value (Value/Benefits), the presence of E-Government is really wanted by the community because it can be accessed anywhere and at any time so that people don't have to queue at the Tondo Village Office, Mantikulore District, Palu City. However, there are still elderly people or people who do not understand gadgets or technology and prefer to come directly to the Tondo Village Office to handle files, as well as Human Resources who are less competent so that the implementation of E-Government at the Tondo Village Office is still a little lacking Maximum.